Simulation on transdermal patch for breast cancer therapy by using COMSOL - Tan, Ming Sien (2010)
Breast cancer is the most common form of cancer affecting women in Malaysia. Conventional drug treatment for breast cancer, chemotherapy would destroy the cancer cells because of the medicine targets on rapidly dividing cells. However, healthy cells and tissues in blood, mouth, intestinal tract, nose, nails, vagina and hair also divide rapidly, they could be damaged. A more promising technology called transdermal patch has been introduced due to side effects are common expected results from conventional treatment. Therefore, the aim of this study was to treat breast cancer by delivering drug from transdermal patch precisely and safely to targeted cancer cell so that reducing the side effects and dosage of drug used. The objectives of this study were to determine the drug concentration at breast tumor, to investigate the relationship between drug diffusivity and drug delivery efficiency, and to evaluate the efficiency of drug delivery under other parameters (i.e. deepness of tumor, temporal and spatial placement of transdermal patch). Available software, COMSOL was used in this study. Drug concentrations that able to diffuse and reach tumor in breast were studied. The simulation results showed that there was optimal drug diffusivity for maximum concentration of drug reached tumor in breast. However, below and higher than this drug diffusivity optimal value, the delivery of drug oncentration was poorer when the lesser. Production of microchannels in the skin by microneedle can increase the drug diffusivity and ensure delivery of pharmacologically effective concentration of drug to the targeted site, breast cancer cell. Deeper the tumor grown within breast, lesser drug‟s concentration could be diffused to it. However, this could be solved by changing the place of transdermal patch application. The nearer the spatial placement of transdermal patch to tumor growth in the breast on the breast skin increased the effectiveness of drug delivery to tumor. The longer the temporal placement resulted in higher drug concentration could be delivered to breast tumor. However, this constant concentration gradient only achieved for less than one month. After this, the concentration gradient would become zero. As a conclusion, the drug diffusivity, deepness of breast tumor, spatial and temporal placement of transdermal patch must be taken into account when engineering, constructing and applying the transdermal patch in order to achieve the maximum breast cancer treatment with reducing the undesired side effects.